Factors associated with 30-day readmission of patients with heart failure from a Japanese administrative database. Issue 1 (December 2015) - Aizawa, Hiroki; Imai, Shinobu; Fushimi, Kiyohide
Abstract Background Numerous studies have been conducted in many countries to identify the factors associated with readmission of patients with heart failure (HF). However, there have been no such studies utilizing a large-scale administrative database in Japan. This study aimed to establish the factors associated with 30-day readmission of patients with HF using a Japanese nationwide administrative database. Methods Data of the index admissions of 68, 257 patients discharged from 1057 participating hospitals between April 1, 2012 and March 31, 2013 were analyzed. Patients were divided into the 30-day readmission group and no readmission group according to whether unplanned HF readmission occurred within 30 days after discharge. Study variables included age, sex, New York Heart Association functional class (NYHA) at admission, Charlson Comorbidity Index (CCI), length of stay in hospital (LOS), body mass index (BMI) at admission, hospital volume reflected by the number of cases hospitalized with HF, and medical treatment at discharge. Results The 30-day readmission and no readmission groups included 4479 and 63, 778 patients, respectively. The independent factors associated with the increase in 30-day readmission were older age, higher NYHA, higher CCI, and use of the following drugs at discharge: beta blockers, loop diuretics, thiazide, and nitrates. In contrast, the independent factors associated with the decrease in 30-day readmission were longer LOS, higher BMI, and the use of angiotensin converting enzyme inhibitors (ACEs) or angiotensin II receptor blockers (ARBs), calcium channel blockers, and spironolactone. Conclusions The results suggest that, especially during the first few weeks after discharge, careful management of HF outpatients with advanced age, high disease severity, multiple comorbidities, or taking beta blockers, loop diuretics, thiazide, and nitrates at discharge may be crucial for reducing the 30-day readmission rate.